Analysis and Comparison of Robotics 3D Simulators - Melo, Mirella; Neto, José; Lima, Pedro Jorge; Teixeira, João Marcelo; Teichrieb, Veronica (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2019: Anais do XXI Simpósio de Realidade Virtual e Aumentada, 2019)
Validating robotics projects is a hard task. It demands more than intellectual effort, but also specific hardware usage, turning the designed project expensive and because of that, unviable to be executed. This process can be improved by the use of 3D simulators, which have been developed directed to scenarios such as architecture, games and virtual reality experiences, and can also be applied to robotics. There are available many 3D simulator options in the market, paid or free. Considering the 3D simulator options, a robotics project designer may have questions on how to choose the best suitable one. From that, this paper intends to analyze these software focusing on robotics simulation, proposing to clarify some questions and guide the simulator choice. After a literature review made in two stages (a more general search regarding 3D simulators and then the final choice considering abstract and conclusion), it was possible to choose the three most used ones by the robotic community: V-Rep, Gazebo, and Unity. We made a more in-depth study about them in order to evaluate and describe important features related to robotics. Later, we also did experiments using each tool intending to analyze terms relative to usability. The experiment consisted of replicating the same standard 3D scene in the three software. Based on the literature review and the experiments, it became possible to punctuate some observations. In terms of usability, V-Rep and Unity presented a significant degree of freedom considering scene editing, besides both having a friendly interface, while Gazebo showed to be more limited and it has a poor user interface. In the three simulators it is possible to perform a connection with ROS, but with different complexities, being Gazebo and V-Rep the easiest ones. They both have more features and facilities when considering developing a robotics project, leaving Unity behind.